Teaching in the Online Classroom : and thriving in the new normal - Lemov, Doug, ....- (Hoboken : Jossey-Bass, 2020)
A timely guide to online teaching strategies from bestselling author Doug Lemov and the Teach Like a Champion team School closures in response to the covid-19 coronavirus pandemic resulted in an immediate and universal pivot to online teaching. More than 3.7 million teachers in the U.S. were suddenly asked to teach in an entirely new setting with little preparation and no advance notice. This has caused an unprecedented threat to children's education, giving rise to an urgent need for resources and guidance. The New Normal is a just-in-time response to educators' call for help. Teaching expert Doug Lemov and his colleagues spent weeks studying videos of online teaching and they now provide educators in the midst of this transition with a clear guide to engaging and educating their students online. Although the transition to online education is happening more abruptly than anyone anticipated, technology-supported teaching may be here to stay. This guide explores the challenges involved in online teaching and guides educators and administrators to identify and understand best practices. It is a valuable tool to help you and your students succeed in synchronous and asynchronous settings this school year and beyond. Learn strategies for engaging students more fully online Find new techniques to assess student progress from afar Discover tools for building online classroom culture, combating online distractions, and more Watch videos of teachers building rigor and relationships during online instruction The New Normal features real-world examples you can apply and adapt right away in your own online classroom to allow you to survive and thrive online.
Doug Lemov and the Teach Like A Champion Team - online lesgeven